Autoimmune bullous diseases in pregnancy: clinical and epidemiological characteristics and therapeutic approach, - Patrícia Penha Silveira Fagundes; Claudia Giuli Santi; Celina Wakisaka Maruta; Denise Miyamoto; Valeria Aoki (Sociedade Brasileira de Dermatologia, 2021)
Abstract Autoimmune bullous dermatoses are a heterogeneous group of diseases with autoantibodies against structural skin proteins. Although the occurrence of autoimmune bullous dermatoses during pregnancy is low, this topic deserves attention, since the immunological and hormonal alterations that occur during this period can produce alterations during the expected course of these dermatoses. The authors review the several aspects of autoimmune bullous dermatoses that affect pregnant women, including the therapeutic approach during pregnancy and breastfeeding. Gestational pemphigoid, a pregnancy-specific bullous disease, was not studied in this review.